Analisis Pengungkapan Akuntansi Lingkungan dan Kinerja Lingkungan terhadap Nilai Perusahaan pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Saputra, Achmad Andika; Maithy, Sifera Patricia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the effect of environmental accounting disclosure and environmental performance on firm value in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research method used is quantitative with a multiple linear regression approach. The data used are secondary data obtained from the annual reports and sustainability reports of the companies sampled in this study, selected using purposive sampling techniques. Environmental accounting disclosure is measured using the environmental cost formula, while environmental performance is measured using the PROPER ratings issued by the Ministry of Environment and Forestry (MoEF). The results of the study show that environmental accounting disclosure and environmental performance have varying effects on firm value, which can be positive, negative, or insignificant. These findings indicate that environmental reporting and management activities do not necessarily add value in the eyes of investors. In certain conditions, these activities may even trigger concerns about additional costs borne by the company, thereby reducing the firm’s value.